CSC645: Algorithm Analysis and Design / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2019)
This course focuses on both the design and analysis of algorithms. It provides students with basic knowledge and techniques required to design efficient algorithms and analyse their efficiency, as well as demonstrate the key relationships between problem solving, algorithm design, data structures, programs and algorithm analysis, and the effects of the choices. This course provides a fundamental platform for the strategies and design ideas of algorithms for solving fundamental problems in computing science.